2008
DOI: 10.2522/ptj.20070196
|View full text |Cite
|
Sign up to set email alerts
|

Motor Learning in Children: Feedback Effects on Skill Acquisition

Abstract: During motor learning, children use feedback in a manner different from that of adults. To optimize motor learning, children may require longer periods of practice, with feedback reduced more gradually, compared with young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
122
7
16

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(159 citation statements)
references
References 41 publications
7
122
7
16
Order By: Relevance
“…A tarefa escolhida foi a de labirinto, que implica em movimentação motora fina para manuseio do teclado do computador por meio de segmentos corporais superiores; portanto, pode ser considerada uma ação motora cotidiana de grande importância nos dias atuais 29 . Na tarefa de labirinto, crianças sem alterações motoras têm como principal desafio escolher o caminho correto; já os indivíduos com PC têm, além da escolha do caminho correto, dificuldade em realizar o movimento.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A tarefa escolhida foi a de labirinto, que implica em movimentação motora fina para manuseio do teclado do computador por meio de segmentos corporais superiores; portanto, pode ser considerada uma ação motora cotidiana de grande importância nos dias atuais 29 . Na tarefa de labirinto, crianças sem alterações motoras têm como principal desafio escolher o caminho correto; já os indivíduos com PC têm, além da escolha do caminho correto, dificuldade em realizar o movimento.…”
Section: Discussionunclassified
“…Os valores foram marcados considerando-se o tempo total da finalização da tarefa, valor fornecido pelo pró-prio programa. Optou-se em utilizar a tarefa -255 -de labirinto no computador, por ser um instrumento tecnológico e facilitador para indivíduos com PC 29 .…”
Section: Procedimentosunclassified
“…En otras palabras, el profesor/entrenador deberá considerar cómo y cuándo dar realimentación, mejor que asumir que más realimentación es mejor. Sin embargo, los niños en edades prepuberales o en madurez temprana pueden necesitar más intentos de práctica con realimentación permanente, comparados con los adultos; esto con el propósito de formar una representación interna de la habilidad estable y precisa, como lo comentan Sullivan, Kantak y Burtner (2008).…”
Section: Consideraciones Finalesunclassified
“…Standing start times (to the nearest 0.01 s) to 60 m for all four starts and an expert-coach subjective rating (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) were recorded at each training session for each of the four standing starts. Additionally, all four standing starts were video recorded.…”
Section: Interventionmentioning
confidence: 99%
“…The co-ordination and control needs to be developed in response to constraints of the particular task [3]. Previous research has shown that throughout the motor skill learning process, instruction, demonstration, imagery and augmented feedback can evoke improvements in the development of sport-specific motor skills [4][5][6][7]. However, for this improvement to take place, the type of instruction delivered, within the ideal practice schedule and accompanied by the correct augmented feedback for the athlete needs to be considered throughout the motor skill acquisition process [8,9].…”
Section: Introductionmentioning
confidence: 99%